1998
DOI: 10.1038/sj.ejcn.1600583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a milk product, fermented by Lactobacillus acidophilus and with fructo-oligosaccharides added, on blood lipids in male volunteers

Abstract: As compared to traditional yogurt, daily consumption of three times 125 ml of test product specifically lowered serum LDL-cholesterol levels in normal healthy male adult subjects with borderline elevated levels of serum total cholesterol within three weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
2
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(101 citation statements)
references
References 12 publications
6
87
2
6
Order By: Relevance
“…The preponderance of fermented milk interventions (Agerback et al, 1995;Schaafsma et al, 1998;Bertolami et al, 1999;Xiao et al, 2003) compared to capsule interventions (Hlivak et al, 2005) demonstrating a hypocholesterolemic effect supports the concept that a dairy medium may be the most efficacious route of administering probiotic bacteria. In vitro simulation has suggested that whereas some species of L. and B. lose viability during gastric transit, ingestion with milk proteins improves their tolerance to the pH of upper GI system (Charteris, 1998).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The preponderance of fermented milk interventions (Agerback et al, 1995;Schaafsma et al, 1998;Bertolami et al, 1999;Xiao et al, 2003) compared to capsule interventions (Hlivak et al, 2005) demonstrating a hypocholesterolemic effect supports the concept that a dairy medium may be the most efficacious route of administering probiotic bacteria. In vitro simulation has suggested that whereas some species of L. and B. lose viability during gastric transit, ingestion with milk proteins improves their tolerance to the pH of upper GI system (Charteris, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…The dose was intended to maximize the potential for a lipid-lowering effect; however, it may have been insufficient. Although an investigation providing a dose of 10 9 CFU of probiotic bacteria via a daily capsule achieved a hypocholesterolemic effect (Hlivak et al, 2005), fermented milk studies demonstrating an effect (Agerback et al, 1995;Schaafsma et al, 1998;Bertolami et al, 1999;Xiao et al, 2003) administered 200-300 ml of product containing 10 7 -10 9 CFU per ml for a total dose of 10 9 -10 11 CFU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fat, protein and dry matter intake did not differ significantly between the placebo and the probiotic periods (Table 2). Earlier studies dealing with the influence of probiotics on cholesterol metabolism have shown contradictory results (Schaafsma et al, 1998;AgerholmLarsen et al, 2000;Jahreis et al, 2002;Kie ling et al, 2002;Lewis and Burmeister, 2005). These contradictions might be caused by different strains and amounts of administered probiotic cultures, no standardized application forms (milk products, sausage and capsules) and varying lengths of treatment periods.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] The majority of randomized controlled trials, however, have reported no significant effect, [20][21][22][23][24][25] and no clinical trial has reported significant LDL-C reductions of a probiotic supplement formulation unless delivered as a synbiotic. 26 Previously, we have reported on the cholesterollowering efficacy of a microencapsulated BSH-active Lactobacillus reuteri NCIMB 30242 yogurt formulation.…”
Section: Introductionmentioning
confidence: 99%